Pengaruh Literasi Keuangan Terhadap Intensi Berinvestasi Dengan Moderasi Self Regulatory Focus - Hakim Manurung; Resi Bramani Y; Immanuel Ricky; Darmanto Darmanto (Universitas Prasetiya Mulya, 2018)
Financial literacy is the understanding, planning and regulation of financial conditions by considering the risks prior to make a decision to invest both in short and long term for the welfare of the individual. Financial literacy has an important role particularly in the decision-making process to invest in financial products. This study examines the extent to which the influence of financial literacy on investment intentions with the Self Regulatory Focus moderation. The results of this study described that when the individual has a higher financial literacy, he or she will tend to have a high intention to invest. Likewise with the moderation of Self Regulatory focus on groups of prevention who have high financial literacy will tend to have a high intention to invest